EFEKTIVITAS KOMITE AUDIT, KUALITAS AUDITOR EKSTERNAL DAN KEMUNGKINAN KECURANGAN PELAPORAN KEUANGAN - Indella, Dwi Rahma; Husaini, Husaini (JURNAL FAIRNESS, 2016)
The purpose of this study was to obtain empirical evidence on the effect of the effectiveness of the audit committee and the quality of the external auditors on the possibility of financial statement fraud.The population in this study are non-financial companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, 104 companies were selected as samples. The sample is categorized into two categories, namely fraud companies and non-fraud firms.This study found that the independent audit committee, the number of audit committee meetings, the expertise of the audit committee, the gender diversity of the audit committee, the ethnicity of the audit committee, and the quality of the external auditors did not affect the likelihood of financial statement fraud. In addition, company size and leverage do not affect the possibility of fraudulent financial statements. Meanwhile, company performance actually affects the possibility of financial statement fraud.